Specificity of long-term management of a woman patient of reproductive age after surgical mitral valve repair against the background of infective endocarditis - E. V. Dren’; I. N. Lyapina; V. I. Ganyukov; A. V. Ivanova; A. N. Stasev; O. L. Barbarash; L. S. Barbarash (Российский кардиологический журнал, 2023)
As a clinical case, we present the "portrait" of a woman patient with acquired mitral valve (MV) defect against the background of infective endocarditis which was diagnosed during the third trimester of pregnancy. The patient underwent mitral valve replacement surgery with biological prosthesis "KemKor" followed by two successful deliveries. In 18 years after the correction of the mitral valve defect, she developed valve prosthesis dysfunction therefore, she underwent endovascular transcatheter implantation of bioprosthesis by method "prosthesis-into-prosthesis" in the mitral position.This clinical case is unique in terms of the reasoning the biological prosthesis choice to correct acquired MV defect in a patient of reproductive age, the long-term period of the bioprosthesis functioning and the correction of further developed valve dysfunction using the techniques of transcatheter implantation.